(untitled) - Ruilova Cueva, María Bernarda; Hernández, Aldho; Niño-Ruiz, Zulay (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Influence of C/N ratio on productivity and the protein contents of Pleurotus ostreatus grown in differents residue mixtures (2017)

(untitled)
The influence of the composition of different agricultural substrates standardized C/N in the productivity and protein content of the fruiting bodies of Pleurotus ostreatus harvested in different mixtures was determined. Six mixtures were designed using the Mixtures of Agricultural Waste for Cultivation of P. ostreatus program, the nitrogen content varied from 0.5 to 1.4%. In three of them, soy flour with a composition of 3, 4 and 6% was used as nitrogen source. The mixtures were categorised according to their physiochemical characteristics, the substrates were adapted and inoculated with the strain 768/12. The best results, 177.37% biological efficiency, 31.13% protein and 2.64 day-1 production rate, this results were achieved with the mixture of 1% nitrogen and 47.99 of C/N form of 15% of rice husks, 40% of lentil stubble, 40% of sugar cane bagasse, 3% of soybean meal and 2% of calcium carbonate, confirming the high dependence of the C/N ratio in the productivity and protein content of P. ostreatus.